Natural course of glutamine synthetase deficiency in a 3 year old patient - Häberle, Johannes; Shahbeck, Noora; Ibrahim, Khalid; Hoffmann, Georg F.; Ben-Omran, Tawfeg (Molecular genetics and metabolism, 2011)
Glutamine deficiency with hyperammonemia due to an inherited defect of glutamine synthetase (GS) was found in a 2year old patient. He presented neonatal seizures and developed chronic encephalopathy. Thus, GS deficiency leads to severe neurological disease but is not always early lethal.
Gesehen am 25.07.2022